RANCANGAN HANDOUT Salmonella sp PADA AYAM PEDAGING (Gallus domesticus) PADA KONSEP EUBACTERIA SMA KELAS X - Ria Dess Septi Laseira; Irda Sayuti; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to use the detection results of Salmonella sp in broilers as a handout design on the eubacteria concept for class X SMA in August-September 2020. This research was conducted in 2 stages, namely the analysis of the potential development of teaching materials for the eubacteria concept of class X SMA, and the design stage. This research was conducted in the laboratory of the Faculty of Teacher Training and Education, University of Riau Pekanbaru. Based on the analysis of the potential research results, it can be used as a handout design on the eubacteria concept of class X SMA. The development of the handout design includes the Analysis and Design stages with a handout structure consisting of cover, introduction (KI and KD 3.5 identifying the structure, way of life, reproduction and the role of bacteria in life, purpose, instructions for use), material description, evaluation questions, and bibliography.Key Words: Salmonella sp, Handout, Eubacteria.